2019
DOI: 10.1002/asna.201913573
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational wave bounds on dirty black holes

Abstract: Detection of gravitational waves has provided a new way to test black hole (BH) models. We show how simple constraints can be obtained for models that go beyond vacuum Einstein gravity solutions of binary BH mergers. Generic stationary metrics, termed dirty BHs in the literature, are not vacuum solutions of the Einstein equations. These models are, however, general enough to describe BHs surrounded by matter fields. Gravitational wave constraints already rule out certain parts of parameter space for these solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…It is strong enough in order not to contribute to the known observations within the solar system and other systems with not too strong gravitational fields [1]. There may be other dependencies with n > 3 and, in fact, in [27,28], it was shown that the fall-off of the dark-energy density has to be stronger. We will discuss other cases of the fall-off, ordered by a number n as in (16); however, the main conclusions and structural predictions of the theory remain similar.…”
Section: The Modified Theory: Pseudo-complex General Relativitymentioning
confidence: 98%
See 3 more Smart Citations
“…It is strong enough in order not to contribute to the known observations within the solar system and other systems with not too strong gravitational fields [1]. There may be other dependencies with n > 3 and, in fact, in [27,28], it was shown that the fall-off of the dark-energy density has to be stronger. We will discuss other cases of the fall-off, ordered by a number n as in (16); however, the main conclusions and structural predictions of the theory remain similar.…”
Section: The Modified Theory: Pseudo-complex General Relativitymentioning
confidence: 98%
“…The two frequencies deduced in (35) and (36) have to be set equal, which leads to the following equation, deduced in [27,28] (we changed the variable r into y = r m 0 and defined a = a m ) √ ∆ y 3 − a 2 F + a 2y 2 m(y)…”
Section: Light-ringsmentioning
confidence: 99%
See 2 more Smart Citations
“…The case n = 2 is ruled out by solar system experiments (Will ), and n = 3 was recently ruled out in (Nielsen & Birnholz , ), investigating the in‐spiral frequency of a gravitational merger. Thus, here, we use n = 4, which is also in line with Visser ()) at large distances.…”
Section: Introduction To Pc‐grmentioning
confidence: 99%